Innovation in the European Value Chain: The Case of the Romanian Automotive Industry - Alina Petronela Negrea; Valentin Cojanu (CES Working Papers, 2015)
Entrepreneurs' and regional stakeholder's capacity to turn knowledge, skills and competencies into sustainable competitive advantage is crucial to a region' economic performance. The article attempts to reveal their synergy by gathering evidence in the particular context of the Romanian automotive industry. Based on primary data collected through structured inter¬views and experiential visits, the research is organized around three investigative themes: (1) entrepreneurs' approach to and perception on innovation, (2) factors affecting innovation, and (3) networking and knowledge diffusion in the regional productive environment. The findings emphasize the convergent opinion of the regional stakeholders on the vital role innovation plays at the current stage of the industry and the key role entrepreneurs have in stimulating innovation in the regional context. A series of three factors underlay the innovative performance at regional and industry level, namely the presence of an innovation friendly business environment, entrepreneurs' personality, as well as the external competitive environment.
Keywords: L62; O3; 330; automotive; entrepreneurship; technology; innovation; Romania